Ferramenta para a avaliação da sustentabilidade em projetos de remediação de áreas contaminadas - Trentin, Adan William da Silva (2020)
Decision-making in the management of contaminated sites has go through a major evolution in recent decades, and more recently there has been an interest in including sustainability as a criterion for decision making. In addition to the primary impacts, associated with the state of the contaminated site, secondary impacts, which are associated with the remediation of the site, have started to be considered in the projects. Thus, sustainable remediation emerges, which considers the impacts and benefits on environmental, economic and social aspects. In line with the growing interest in sustainable remediation, decision support tools have been developed to support remediation specialists and, eventually, policy makers, to select the most sustainable option from the various alternatives available. However, the tools do not yet meet all sustainability assessment criteria, demonstrating that there is space for improvement. In this sense, this study aimed to develop a tool to support decision making to assess the sustainability of projects for the contaminated sites remediation. To this end, the methodology consisted of three main stages: (01) identification and description of the existing tools for assessing the sustainability of projects for the contaminated sites remediation; (02) elaboration of a decision support tool to assess sustainability in remediation projects; and (3) tool validation. The results indicated the existence of sixteen decision support tools developed for the evaluation of projects for contaminated sites remediation. These tools are not fully quantitative in economic and social aspects and the life cycle perspective is not included in the assessment of impacts related to the three pillars of sustainability. Based on the knowledge of the existing tools, the Quantitative Assessment of Life Cycle Sustainability (QUALICS) tool was developed. The QUALICS tool is a combination of two multi-criteria evaluation methods, the Integrated Value Model for Sustainable Assessment (MIVES) and Analytic Hierarchy Process (AHP). The QUALICS uses a multi-criteria assessment framework to support decision-making in remediation projects. Two case studies were discussed to demonstrate the application of QUALICS in assessing the sustainability of different remediation options. The results of its application indicated that the proposed tool can be applied to projects, with different characteristics, to quantify and compare the sustainability indexes of each considered remediation alternatives and, thus, to identify the most sustainable option.